Individual differences in speech monitoring: Functional and structural correlates of delayed auditory feedback - Muge Ozker; Laura Giglio; Ahmad Beyh; Stephanie J. Forkel; Peter Hagoort (Proceedings of the National Academy of Sciences, 2026)
Sensory feedback is essential for the fine-tuning of motor actions, and speech production is no exception. It depends on continuous self-monitoring to ensure that produced sounds match intended targets. Delaying auditory feedback (DAF) disrupts this alignment and impairs fluency, providing a powerful tool to investigate sensorimotor control. We combined functional and diffusion-weighted MRI in 31 participants performing a word-production task under delayed (DAF) and immediate (no-DAF) auditory feedback. While all participants slowed their speech under DAF, the extent of this effect varied across individuals and was quantified using a susceptibility index. At the group level, DAF > no-DAF elicited increased activation in a right-lateralized network encompassing the superior temporal gyrus, supramarginal gyrus, inferior frontal gyrus, supplementary motor area, and left cerebellum. Incorporating individual differences revealed that higher susceptibility was associated with greater activation in left-hemisphere speech motor homologues and larger volume of the right long segment of the arcuate fasciculus, a whitematter pathway connecting auditory and motor speech regions. This pattern suggests that susceptibility reflects increased recruitment of neural resources and a stronger reliance on auditory-motor coupling. In contrast, resilience was associated with greater engagement of the bilateral angular gyrus and higher fiber density in the right posterior AF, which connects auditory and somatosensory speech regions. This finding indicates that resilience is supported by a posterior temporo-parietal circuit that efficiently integrates multimodal sensory feedback. Together, these findings link functional dynamics with underlying structural connectivity to reveal how a right-lateralized network supports speech control, while accounting for individual differences in susceptibility to fluency disruption.